CAPILLARY MODEL OF TREE TRUNKS - Yury M. Vernigorov; Iosif A. Kipnis (Advanced Engineering Research, 2012)
The wa ter lifting mechanism in the tree trunks acting by the surface tension forces in the capillary chann els of var ious diameters and configurations is investigated.